Integrasi Bangsa dan Neo Weberian State (NWS) - Hanafie, Haniah (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2017)
This paper aims to analysis that Indonesia as a strategic country, located between two continents and two oceans. Indonesia is high populations and has rich natural resources, so that it can be coveted by other countries. In 2043, Indonesia to be threatment from other world, because there has been a crisis of food availability, clean water, and energy. The influence of global era, open markets and liberal economic system have affected decreasing Indonesia’s nationalism (disintegration), made high poverty, lower of social welfare and only give the advantage toward capitalist groups. In addition, domestic issues, such as the SARA issue, are easily explored, resulting in political conflicts. The domestic, international and global problems will be the main conflict if it did not manage well and can to be disintegration of nations impact. Therefore, New Weberian State (NWS) Concept is expected to be a solution to prevent disintegration of Indonesia nations. NWS one of model for development countries with instruments rational, efficiency, effective, accountability and eigh principal to be implemented :1). Centrality of the State, 2). Reform and Enforcement of Administrative Law, 3). Preservation of Public Service, 4). Representative Democracy, 5). External Orientation Toward Citizens, 6). Supplemental Public Consultation and Direct Citizen Involvement, 7). Results Orientation, 8). Management Professionalism.